PERAN EMOTIONAL RESPONSE KONSUMEN DALAM MEMEDIASI PENGARUH STORE ENVIRONMENT TERHADAP IMPULSE BUYING (SURVEI PEMBELI DI CARREFOUR KOTA DENPASAR) - Putra, Arya Diana; Sukawati, Tjok Gde Raka (E-Jurnal Manajemen; Vol 4 No 1 (2015), 2015)
The purpose of this study was to determine the role of emotional response in the consumer environment to mediate the effect of store impulse buying is done at the buyer at Carrefour Denpasar. This study uses qualitative research is by using observation and questionnaires to 140 buyers in Carrefour Denpasar. The data analysis technique used is structural equation modeling (SEM). Obtained findings that the store environment variable positive and significant impact on impulse buying and store environment variable positive and significant effect on positive emotions. Furthermore, it was found that the emotional response variables and significant positive effect on impulse buying. Finally, the emotional response in mediating store significant effect on the environment of impulse buying.
Keywords: Emotional Response; Store Environment; Impulse Buying